Dynamics of Sill and Laccolith Emplacement in the Brittle Crust: Role of Host Rock Strength and Deformation Mode. Issue 11 (6th November 2017) - Schmiedel, T.; Galland, O.; Breitkreuz, C.
Abstract: Igneous intrusions in sedimentary basins exhibit a great diversity of shapes from thin sheets (e.g., dikes, sills and cone sheets) to massive intrusions (e.g., laccoliths and plugs). Presently, none of the established models of magma emplacement have the capability to simulate this diversity because they account for either purely elastic or purely plastic or purely viscous host rocks, whereas natural rocks are complex visco‐elasto‐plastic materials. In this study, we investigate the effects of elasto‐plastic properties of host rock on magma emplacement using laboratory experiments made of dry granular materials of variable cohesion. Our results show how the deformation mechanism of the host rock controls the emplacement of magma: thin sheet sills form in high‐cohesion materials, which dominantly deform by elastic bending, whereas massive intrusions such as punched laccoliths form in low‐cohesion materials, which dominantly deform by shear failure. Our models also suggest that combined elastic/shear failure deformation modes likely control the emplacement of cone sheets. Our experiments are the first to spontaneously produce diverse, geologically relevant intrusion shapes. Our models show that accounting for the elasto‐plastic behavior of the host rock is essential to filling the gap between the established elastic and plastic models of magma emplacement, and so to reveal the dynamics of magma emplacement in the Earth's brittle crust. Key Points: First laboratory models that simulate both sheet and massive magma intrusions Intrusion shape correlates with host material strength and deformation mode Elasto‐plastic host rock rheology is required to reveal magma emplacement mechanism